APLIKASI NOZEL PADA DUA VARIETAS KENTANG UNTUK PRODUKSI BENIH SECARA AEROPONIK - Eni sumarni (Jurnal Biofisika, 2014)
Seed is a major problem for potato growers in Indonesia. Therefore, the acceleration of seed potato production is needed to reduce dependence on imports. One of the important things in the aeroponic system is a good oxygenation of each grain fog nutrient solution to the plant roots. The purpose of this study is to get a good nozzle type on nutrition aeroponic system. Seed potatoes used are varieties of Granola and Atlantic. Factors tested: type of nozzle (N) : N1 (spray jet blue : 55 lt/ h, beam diameter (d): 2,4 m), N2 (green jet spray : 90 lt/h, d : 3,2 m), N3 (microsprays black yellow : 70 lt/h, d: 1 m). Research using a randomized block design with three replications. Analysis of the data using analysis of variance followed by Duncan's multiple range test at level 5 %. The results showed that the use of a good nozzle on aeroponics system is the specification 55 l/h nozzle, d: 2,4 m and 90 lt/h, d: 3,2 m. Microsprayer with specification of 70 llt/h, d: 1 m is less suitable because it has less spread bursts specification. Varieties of potato plants that provide both growth and yield up to 65 days after planting is Granola.